2013
DOI: 10.1002/ange.201303489
|View full text |Cite
|
Sign up to set email alerts
|

Turning Coacervates into Biohybrid Glass: Core/Shell Capsules Formed by Silica Precipitation in Protein/Polysaccharide Scaffolds

Abstract: Kern‐Schale‐Biohybridkapseln (siehe Bild), die flüchtige Verbindungen verkapseln können, entstehen durch Fällung von amorphem Siliciumdioxid in einem Protein‐Polyanion‐Koazervatgerüst. Dieses Gerüst gibt der Kapselhülle ihre endgültige Form und Struktur und stellt eine acide Mikroumgebung bereit, in der die Hydrolyse und Kondensation flüssiger Siliciumdioxidvorstufen lokal induziert werden können.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Coacervate micro-droplets are produced by liquid–liquid phase separation and exhibit a range of biomimetic properties such as selective molecular uptake, 7 , 8 micro-compartmentalized nanoparticle 9 or enzyme catalysis, 10 in vitro gene expression, 11 , 12 and templating of lipid membrane multilayer assembly. 13 Although recent studies have used auxiliary components such as inorganic nanoparticles, 14 inorganic polyanionic clusters, 15 covalent crosslinking, 16 , 17 and hydrogels 18 , 19 to produce higher-order coacervate-based micro-architectures, the use of coacervate micro-droplets as an intrinsic, structurally reconfigurable micro-compartmentalized phase has been rarely exploited. 20 Coacervates based on polymer/small molecule (monomer) complexation show considerable promise as reconfigurable protocells because the relative weakness of the electrostatic interactions increases the scope to structurally and compositionally manipulate the micro-droplets by environmental triggers such as changes in salt concentration, pH and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Coacervate micro-droplets are produced by liquid–liquid phase separation and exhibit a range of biomimetic properties such as selective molecular uptake, 7 , 8 micro-compartmentalized nanoparticle 9 or enzyme catalysis, 10 in vitro gene expression, 11 , 12 and templating of lipid membrane multilayer assembly. 13 Although recent studies have used auxiliary components such as inorganic nanoparticles, 14 inorganic polyanionic clusters, 15 covalent crosslinking, 16 , 17 and hydrogels 18 , 19 to produce higher-order coacervate-based micro-architectures, the use of coacervate micro-droplets as an intrinsic, structurally reconfigurable micro-compartmentalized phase has been rarely exploited. 20 Coacervates based on polymer/small molecule (monomer) complexation show considerable promise as reconfigurable protocells because the relative weakness of the electrostatic interactions increases the scope to structurally and compositionally manipulate the micro-droplets by environmental triggers such as changes in salt concentration, pH and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Erni et al synthesized microcapsules with dense walls composed entirely of a biopolymer scaffold interpenetrated with amorphous silica. [ 37 ] A weakly acidic hydrogel shell was first formed around oil droplets, which then served as a scaffold to induce protein‐directed mineralization of silica. The precipitation process, occurring in the hydrogel scaffold, consumed water to form silica, yielding dense shells with a very low permeability for volatile organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, biomimetic templating methods have emerged as relatively new approaches to synthesize silica-based nanocarriers owing to the abilities of mineralizing biomolecules to recognize, interact with, and direct the nucleation and growth of silica under physiological conditions. For example, Jakhmola et al synthesized oil-core silica-shell nanocapsules, thereby using a layer-by-layer assembly method in which oppositely charged biomolecules were alternately deposited on a nanoemulsion template followed by silica mineralization . Erni et al reported the synthesis of silica capsules having a diameter at a scale of hundreds of micrometers by silicification of cross-linked coacervate of gelatin and Acacia gum around oil droplets …”
Section: Introductionmentioning
confidence: 99%